Evaluation of correctional services libraries in offender rehabilitation programmes in Gauteng Province, South Africa - Molala, Mmakwena Raymond (My University, 2022)
Correctional services libraries have a bigger role to play in offender rehabilitation programmes in South African correctional services centres (CSC’s). However, the literature studies on the restoration and rehabilitation of inmates in South Africa barely mentions the role of correctional services’ libraries’ in offender rehabilitation programmes. The aim of this study was to evaluate the correctional services libraries in terms of offender rehabilitation programmes in Gauteng province, South Africa. The objectives of the study were to analyse whether the correctional services library policies aligns to the support of correctional services rehabilitation programmes; to assess the performance of the correctional services libraries in terms of services and programmes, staff qualifications, resources and access to information for the inmates; to determine the correctional services library management support to the correctional services librarians; and to establish if there was proper access to the correctional services libraries in terms of physical facilities and information and communications technology (ICT) infrastructure. The study adopted a qualitative research approach and used semi-structured mediated interviews for data collection. The targeted population for the study was sixteen (16) offender librarians within various correctional centre facilities in Gauteng province, of those, librarians from twelve (12) correctional centres participated. Data were analysed thematically.The major findings of the study revealed that there was no written library CSC policy in any of the CSC libraries, and that offender librarians reported to the Department of Basic Education and the Department of Sports, Recreation, Arts and Culture (DSRAC). Furthermore, offender libraries were resourced in terms of publications and providing information and recreational support to the inmates, including inmates in restricted houses and the disabled. However, in respect to the educational qualifications of librarians attached to prisons libraries, it was found that most did not have requisite Library and Information Science qualifications. CSC libraries’ floor planning varied and no ICT facilities were available for inmates to access information. The study recommends that the Department of Correctional Services (DCS) through its Act (Act no 11 of 1998) should provide clear guidance on access to information and reading materials; formaualte prison LIS policies and review its policy to employ qualified librarians; ensure its libraries have access to ICT’s for inmates, thus allowing transfer of skills; and stipulate that new CSC’s built in South Africa must do their floor planning as per International Federation of Libraries and Information Services Association (IFLA) Guidelines for Library Services to Prisoners (Lehman & Locke 2005).
Thesis (M. A. (Information Studies)) -- University of Limpopo, 2022
Keywords: Correctional services libraries; Prison libraries; Offender rehabilitation programmes; Gauteng province; South Africa; Criminals; Criminals -- Rehabilitation -- South Africa; Criminals -- Rehabilitation; Special libraries